2021
DOI: 10.1002/ehf2.13386
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and prognosis of right ventricular function in pulmonary hypertension due to heart failure with reduced ejection fraction

Abstract: Aims Failure of right ventricular (RV) function worsens outcome in pulmonary hypertension (PH). The adaptation of RV contractility to afterload, the RV-pulmonary artery (PA) coupling, is defined by the ratio of RV end-systolic to PA elastances (Ees/Ea). Using pressure-volume loop (PV-L) technique we aimed to identify an Ees/Ea cut-off predictive for overall survival and to assess hemodynamic and morphologic conditions for adapted RV function in secondary PH due to heart failure with reduced ejection fraction (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…By analyzing the morpho-functional parameters of the right chambers, right atrial dilation is found to be closely associated with congestion, both clinical and instrumental. PH, RVD and ventricular/arterial decoupling represent the triggering and maintenance factors of the right chamber's dilation and should be considered as an indirect US sign of elevated pulmonary pressure and RAP, measured invasively, as already noted in previous studies [11,21]. This dynamic condition is associated with the further worsening of the right ventricular function, regardless of LVEF, triggering a vicious circle of "chamber dilation-increased filling pressures-tricuspid insufficiency-arrhythmias".…”
Section: Discussionmentioning
confidence: 67%
“…By analyzing the morpho-functional parameters of the right chambers, right atrial dilation is found to be closely associated with congestion, both clinical and instrumental. PH, RVD and ventricular/arterial decoupling represent the triggering and maintenance factors of the right chamber's dilation and should be considered as an indirect US sign of elevated pulmonary pressure and RAP, measured invasively, as already noted in previous studies [11,21]. This dynamic condition is associated with the further worsening of the right ventricular function, regardless of LVEF, triggering a vicious circle of "chamber dilation-increased filling pressures-tricuspid insufficiency-arrhythmias".…”
Section: Discussionmentioning
confidence: 67%
“…The prognosis of HF depends essentially on the nature of the underlying heart disease and the presence or absence of triggering factors. There is increasing recognition of the crucial role of the RV in determining prognosis in multiple conditions [ 58 , 59 ]. It is associated with poor clinical outcomes independently of the underlying mechanism: across the spectrum of LVEF, in patients with acute and chronic left HF, acute coronary syndromes, after cardiac surgery and congenital heart disease.…”
Section: Diagnosis and Prognosismentioning
confidence: 99%
“…End-systolic ventricular elastance (E es ) and arterial elastance (E a ) reflect the contractility and afterload of the RV, respectively. While E es /E a ratio is correlated with the RV-PA coupling, [ 34 ] invasive assessment methods to obtain E es /E a using cardiac catheterization remain challenging. Importantly, the RV and PA should be studied together in the evaluation of CTEPH.…”
Section: Assessment Of the Rv Afterload And Function In Ctephmentioning
confidence: 99%